Antidiabetic Activity, Phytochemical Analysis, and Acute Oral Toxicity Test of Combined Ethanolic Extract of Syzygium polyanthum and Muntingia calabura Leaves - Agustinus Widodo; Evi Sulastri; Ihwan Ihwan; Mohamad Hadi Cahyadi; Saipul Maulana; Muhammad Sulaiman Zubair (The Scientific World Journal)
Syzygium polyanthum is known for its capacity to regulate blood glucose levels in individuals with diabetes, while Muntingia calabura leaves have a traditional history as an alternative therapy due to their antidiabetic compounds. The combination of these two plants is expected to yield more optimized antidiabetic agents. This study aims to assess the antidiabetic activity of the combined ethanolic extract of S. polyanthum and M. calabura leaves by measuring the in vitro inhibition of the α-glucosidase enzyme and the blood glucose level in streptozotocin-induced rats and to determine the phytochemical contents of total phenolics, total flavonoids, and quercetine as marker compounds. Acute oral toxicity test was also evaluated. Both plants were extracted by maceration using 96% ethanol. Various combinations of S. polyanthum and M. calabura leaves extracts (1 : 1, 2 : 1, 3 : 1, 1 : 3, and 1 : 2) were prepared. The in vitro test, along with the total phenolic and total flavonoid content, were measured by using UV-Vis spectrophotometry, while quercetine levels were quantified through high-performance liquid chromatography (HPLC). The in vivo and acute toxicity tests were performed on rats as an animal model. The findings demonstrated that the 1 : 1 combination of S. polyanthum and M. calabura leaves ethanolic extract displayed the highest enzyme inhibitory activity with IC50 value of 36.43 µg/mL. Moreover, the combination index (CI) was found <1 that indicates the synergism effect. This combination also decreases the blood glucose level in rats after 28 days of treatments without significant difference with positive control glibenclamide (p>0.005), and it had medium lethal doses (LD50) higher than 2000 mg/kg BW. Phytochemical analysis showed that the levels of total phenolics, total flavonoids, and quercetine were 30.81% w/w, 1.37% w/w, and 3.25 mg/g, respectively. These findings suggest the potential of combined ethanolic extracts of S. polyanthum and M. calabura leaves (1 : 1) as raw materials for herbal antidiabetic medication.